2018
DOI: 10.1002/ijc.31291
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between the CYP2D6 polymorphisms and tamoxifen efficacy in adjuvant endocrine therapy of breast cancer patients in Chinese Han population

Abstract: Variants of the CYP2D6 gene may lead to a poor prognosis of tamoxifen (TAM)-treated patients. Our study validated the association between the CYP2D6 genotype and outcomes of patients receiving TAM in adjuvant endocrine therapy. A total of 778 breast cancer patients who received adjuvant TAM (n = 325) or aromatase inhibitors (AIs) (n = 453) at the National Cancer Center were analyzed. Nine single nucleotide polymorphisms (SNPs) in the CYP2D6 gene were selected from online databases. The associations of each SNP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 21 publications
(21 reference statements)
2
25
0
Order By: Relevance
“…We previously conducted a study to confirm this phenomenon. Our findings showed that Chinese breast cancer patients with the CYP2D6 *10 T/T genotype had worse clinical outcomes when receiving adjuvant TAM treatment …”
Section: Introductionmentioning
confidence: 66%
See 4 more Smart Citations
“…We previously conducted a study to confirm this phenomenon. Our findings showed that Chinese breast cancer patients with the CYP2D6 *10 T/T genotype had worse clinical outcomes when receiving adjuvant TAM treatment …”
Section: Introductionmentioning
confidence: 66%
“…A total of 167 (21.5%) patients carried the CYP2D6 *10 T/T genotype. Among the patients who received TAM, the 5‐year DFS rate was considerably lower in CYP2D6 *10 T/T genotype patients than in C/C or C/T patients ( p = 0.007) …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations